2011
DOI: 10.1016/j.healthplace.2010.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent smoking risk increases with wider income gaps between rich and poor

Abstract: Data from a state-wide survey of California middle and high school students (N=20,203) were used to assess whether county income inequality and poverty rates were associated with adolescent smoking. Greater county income inequality, but not poverty rates, was associated with higher established smoking risk (p= 0.0019). The association was stronger in males than females, whites than other ethnic groups, and urban than rural settings. Neither county income inequality nor poverty rates were associated with experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 41 publications
1
25
0
2
Order By: Relevance
“…Other studies report a positive relationship between income, in particular having access to discretionary income (Hong, Rice, & Johnson, 2011), and cigarette use (Ben Lakhdar, Cauchie, Vaillant, & Wolff, 2012). Further, the effect of income on adolescent cigarette use may not be limited to the adolescents’ family and personal income, but aspects of the broader community's income may also play a role in the regular smoking among this age group (Mistry et al, 2011). …”
Section: Other Substance Usementioning
confidence: 99%
“…Other studies report a positive relationship between income, in particular having access to discretionary income (Hong, Rice, & Johnson, 2011), and cigarette use (Ben Lakhdar, Cauchie, Vaillant, & Wolff, 2012). Further, the effect of income on adolescent cigarette use may not be limited to the adolescents’ family and personal income, but aspects of the broader community's income may also play a role in the regular smoking among this age group (Mistry et al, 2011). …”
Section: Other Substance Usementioning
confidence: 99%
“…Among adolescents (mean age 15), higher income inequality at the county-level predicted elevated prevalence of smoking among white and Hispanic boys but not among African Americans or girls. 45 Importantly, all three studies relied on self-reported measures of smoking, and did not examine exposure to SHS.…”
Section: Introductionmentioning
confidence: 99%
“…É neste período que os adolescentes definem o seu estilo de vida e podem iniciar o consumo regular de tabaco até à idade adulta 5 . Nesta transição, os adolescentes estão expostos a fases de risco, inadaptação e provação 6 .…”
Section: Introductionunclassified